Cyberbullying, well-being, and mental health of freshmen of a University in Bangkok - Jamnongrit, Thachira (Chulalongkorn Medical Journal, 2022)
Background: Cyberbullying is an electronic harassment commonly found in adolescents and affects the wellbeing and mental health of the victims. Objective: The purpose of this study was to estimate the prevalence of cyberbullying among freshman and to investigate the relationship between cyberbullying, psychological well-being, and mental health among freshmen of Chulalongkorn University. Methods: A cross-sectional design enrolled participation of 1,433 freshmen in 19 faculties of Chulalongkorn University. The subjects were requested to complete online surveys concerning demographic information, cyber-aggression victimization scale (Thai version), Thai mental health questionnaire (TMHQ: CU-modified version), and CU student psychological well-being (revised 2020). Results: Fifty-two point-seven percent of freshmen gained experience of cyberbullying; 25.5% of all subjects had low psychosocial well-being, and 44.2% were inclined to have mental health problems. Cyberbullying was associated with lower psychosocial well-being, as well as significantly increased somatization, depression, anxiety and psychotic symptoms. Conclusion: Cyberbully victims reported lower well-being and poor mental health than those who had no experience of it. These findings indicated that cyberbullying could occur among college students and initiatives to prevent cyber-aggression and its consequences were required.